(untitled) - Copeland, Thomas E. (Reading, Massachusetts, 1988)
The book discusses the six seminal and internally consistent theories upon which modern finance: utility theory, state-preference theory, mean-variance theory and the capiltal asset pricing model, arbitrage pricing theory, option pricing theory, and the Modigliani-Miller theorems. Finally, inaddition to the theory and empirical evidence there is always the practical question of how to apply the concepts to difficult and complex realworld problems
Keywords: Corporations; Finance